HEMODİYALİZ HASTALARINDA BESLENME DURUMU VE DİYALİZ YETERLİLİĞİ ARASINDAKİ İLİŞKİ - KALENDER, Betül; ERDOĞAN, M. Sarper; ŞENGÜL, Erkan; SERDENGEÇTİ, Kamil and EREK, Ekrem and YILMAZ, Ahmet (Cerrahpaşa Medical Journal, 2019)
Background and Design.- Malnutrition and inadequate dialysis are associated with increased morbidity and mortality in hemodialysis (HD) patients. In this study our aim was to assess nutritional status and adequacy of dialysis in HD patients. Thirty four HD patients (17 male, 17 female) and 41 healthy (21 male, 20 female) controls were enrolled. Twenty two patients were followed at our Dialysis Unit, Department of Nephrology, Medical Faculty, Kocaeli University, twelve patients were followed at the Dialysis Unit, Department of Nephrology, Cerrahpaşa Medical Faculty, Istanbul University. In HD patients mean age was 51±18 (range 16-76) years and median time on dialysis was 10 (minumum 6-maximum 264) months. In healthy volunteers mean age was 44±12 years. Anthropometrics measurements such as body mass index (BMI), triceps skinfold thickness (TST), mid-arm circumference (MAC) was done in HD patients and controls. Dietary protein and calorie intake were calculated by means of a food reports to be recorded by the patients. Duration of food report was 3 days. Hemoglobin, hematocrit, serum urea, creatinine, albumin, total cholesterol, potassium, calcium, phosphorus, alkaline phosphatase, intact parathyroid hormone, immunoglobulins, complement, iron, total iron-binding capacity, ferritin concentrations, blood pH and bicarbonate were measured and transferrin, normalized protein catabolic rate (nPCR), urea reduction ratio (URR), Kt/V were calculated in the patients. Statistical analysis was performed with the SSPS (Statistical Package for Social Science) for Windows Version 10.0 system using Student.s t test, Pearson correlations and Mann-Whitney U test. Results.- The mean BMI, TST and MAC values were lower in the HD patients compared to the control group (p<0.05). There was significant correlation between BMI and TST, BMI and MAC, TST and MAC in HD patients (p<0.05). No significant correlation was found between antropometric values and nutritional parameters (p>0.05). There was significant correlation between nPCR as a nutritional marker and URR, Kt/V (Jindal) and Kt/V (Daurgidas) as adequacy of dialysis markers (p<0.05). There was significant correlation between albumin and creatinine, nPCR and urea, phosphorus and urea, phosphorus and creatinine, phosphorus and potassium (p<0.05). Conclusion.- In conclusion mild protein malnutrition was present in our patients with inadequate protein intake. In addition targeted adequacy of dialysis was not achieved. For these reasons, in HD patients should be monitored nutritional status and adequacy of dialysis and measures should be taken as necessary.